Clinical Application of Ultrahigh-Field-Strength Wrist MRI: A Multireader 3-T and 7-T Comparison Study - Heiß, Rafael; Weber, Marc-Andre; Balbach, Eva; Schmitt, Rainer; Rehnitz, Christoph; Laqmani, Azien; Sternberg, Andreas; Ellermann, Jutta J.; Nagel, Armin Michael; Ladd, Mark E.; Englbrecht, Matthias; Arkudas, Andreas; et al. (Radiology, 2023)
Background Ultrahigh-field-strength MRI at 7 T may permit superior visualization of noninflammatory wrist pathologic conditions, particularly due to its high signal-to-noise ratio compared with the clinical standard of 3 T, but direct comparison studies are lacking. Purpose To compare the subjective image quality of 3-T and 7-T ultrahigh-field-strength wrist MRI through semiquantitative scoring of multiple joint tissues in a multireader study. Materials and Methods In this prospective study, healthy controls and participants with chronic wrist pain underwent 3-T and 7-T MRI (coronal T1-weighted turbo spin-echo [TSE], coronal fat-suppressed proton-density [PD]-weighted TSE, transversal T2-weighted TSE) on the same day, from July 2018 to June 2019. Images were scored by seven musculoskeletal radiologists. The overall image quality, presence of artifacts, homogeneity of fat suppression, and visualization of cartilage, the triangular fibrocartilage complex (TFCC), and scapholunate and lunotriquetral ligaments were semiquantitatively assessed. Pairwise differences between 3 T and 7 T were assessed using the Wilcoxon signed-rank test. Interreader reliability was determined using the Fleiss kappa. Results In total, 25 healthy controls (mean age, 25 years ± 4 [SD]; 13 women) and 25 participants with chronic wrist pain (mean age, 39 years ± 16; 14 men) were included. Overall image quality (P = .002) and less presence of artifacts at PD-weighted fat-suppressed MRI were superior at 7 T. T1- and T2-weighted MRI were superior at 3 T (both P < .001), as was fat suppression (P < .001). Visualization of cartilage was superior at 7 T (P < .001), while visualization of the TFCC (P < .001) and scapholunate (P = .048) and lunotriquetral (P = .04) ligaments was superior at 3 T. Interreader reliability showed slight to substantial agreement for the detected pathologic conditions (κ = 0.20-0.64). Conclusion A 7-T MRI of the wrist had potential advantages over 3-T MRI, particularly in cartilage assessment. However, superiority was not shown for all parameters; for example, visualization of the triangular fibrocartilage complex and wrist ligaments was superior at 3 T. © RSNA, 2023 Supplemental material is available for this article.
CRIS-Team Scopus Importer:2023-04-21